Novel pathogenically oriented surgical technique for advanced glaucoma - A.Yu. Kazantzeva (РМЖ "Клиническая офтальмология")
A.Yu. Kazantseva Pirogov Russian National Research Medical University, Moscow, Russian Federation For many experts, the choice of management strategy for glaucoma is still controversial. Adequate intraocular pressure (IOP) lowering slows the progression of glaucomatous optic neuropathy and preserves vision. IOP-lowering agents and laser treatment for glaucoma are widely adopted, however, they provide short-term IOP-lowering effect. Most surgeons are forced to choose between penetrating and minimally invasive non-penetrating procedures. Fistulizing glaucoma surgery is highly effective in terms of rapid IOP lowering. However, they are associated with intra- and postoperative complications resulting in impaired vision and requiring medical treatment and even surgery. Non-penetrating procedures provide gradual IOP lowering. Surgical resection of sclera is a novel surgical technique which improves uveoscleral outflow, reduces IOP, and prevents intra- and postoperative complications due to its minimum invasiveness. Considering this, one can postulate that this procedure is recom mended for patients with low vision or monocular patients. Keywords: glaucoma, surgical resection of sclera, uveoscleral outflow, intraocular pressure, IOP, coefficient of outflow facility, non-penetrating surgery, postoperative complications. For citation: Kazantseva A.Yu. Novel pathogenically oriented surgical technique for advanced glaucoma. Russian Journal of Clinical Ophthalmology. 2020;20(1):–25. DOI: 10.32364/2311-7729-2020-20-1-21-25.